Endoscopic transoral outlet reduction induces enterohormonal changes in patients with weight regain after Roux-en-Y gastric bypass - Brunaldi, Vitor Ottoboni; Farias, Galileu Ferreira; de Moura, Diogo Turiani Hourneaux; Santo, Marco Aurélio; Abu Dayyeh, Barham K.; Faria, Caroline Silverio; Antonangelo, Leila; Waitzberg, Dan Linetzki; de Moura, Eduardo Guimarães Hourneaux (Endoscopy International Open, 2024)
Background and study aims Transoral outlet reduction (TORe) has long been employed in treating weight regain after Roux-en-Y gastric bypass. However, its impact on gut hormones and their relationship with weight loss remains unknown.Patients and methods This was a substudy of a previous randomized clinical trial. Adults with significant weight regain and dilated gastrojejunostomy underwent TORe with argon plasma coagulation (APC) alone or APC plus endoscopic suturing (APC-suture). Serum levels of ghrelin, GLP-1, and PYY were assessed at fasting, 30, 60, 90, and 120 minutes after a standardized liquid meal. Results were compared according to allocation group, clinical success, and history of cholecystectomy.Results Thirty-six patients (19 APC vs. 17 APC-suture) were enrolled. There were no significant baseline differences between groups. In all analyses, the typical postprandial decrease in ghrelin levels was delayed by 30 minutes, but no other changes were noted. GLP-1 levels significantly decreased at 12 months in both allocation groups. Similar findings were noted after dividing groups according to the history of cholecystectomy and clinical success. The APC cohort presented an increase in PYY levels at 90 minutes, while the APC-suture group did not. Naïve patients had significantly lower PYY levels at baseline (P = 0.01) compared with cholecystectomized individuals. This latter group experienced a significant increase in area under the curve (AUC) for PYY levels, while naïve patients did not, leading to a higher AUC at 12 months (P = 0.0001).Conclusions TORe interferes with the dynamics of gut hormones. APC triggers a more pronounced enteroendocrine response than APC-suture, especially in cholecystectomized patients.
Keywords: Endoscopy Upper GI Tract; GI surgery